Productivity of potato-boro rice cropping pattern in Haor ecosystem - Karim, Md Mahboob; Bhuiya, Md Sultan Uddin; Hossain, SM Altaf (Research in Agriculture Livestock and Fisheries, 2015)
A study was conducted at PurbaTethulia village, in Dingaputa haor of Mohangonj Upazila in Netrakona district during the period from October 2011 to April 2012. The objective of the study was to diversify and intensify crops in the research site and to develop a more productive cropping pattern. In the trial, Potato-Boro rice-Fallow cropping pattern was followed. The experiment was laid out in a randomized complete block design with five replications. The agronomic productivity (rice equivalent yield t ha-1) of the Potato-Boro rice-Fallow cropping pattern was 24.32 t ha-1with economic productivity (gross margin Tk ha-1) of 163210 and the benefit cost ratio of 1.80. Potato-Boro rice pattern may be disseminated in haor areas of similar environment. Res. Agric., Livest. Fish.2(2): 247-251, August 2015